Enhancing Hungarian language learning - Gnitiev, Sergei (Vestnik za tuje jezike, 2025)
This paper lays the groundwork for future research on the effectiveness of integrating translanguaging methodology into Hungarian as a Foreign Language (HFL) classrooms. Over time, language learning has undergone significant shifts: from frontal, monolingual instruction, typically delivered in the learners’ native language and centred on grammar drills, to full-immersion approaches where teachers exclusively use the target language to develop comprehension and fluency. While immersion methods have gained recognition, they often restrict learners from drawing on their full linguistic repertoires. In contrast, translanguaging embraces multilingual resources as pedagogical tools. Cenoz and Gorter (2011, 2017) strongly advocate for the use of translanguaging in educational contexts, arguing that it fosters deeper and more effective language acquisition.The present study aims to enrich HFL curricula by introducing translanguaging-based practices that encourage learners to draw flexibly on all of their linguistic knowledge. The practical component of this research considers a diverse group of students enrolled in higher education programs, who must achieve specific HFL proficiency levels as part of their academic requirements. Within this context, the study investigates how translan-guaging strategies can facilitate both communicative competence and academic success.The primary challenge addressed is the limited promotion of translanguaging in current HFL instruction, which remains heavily reliant on traditional methods. By exploring feasible strategies for incorporating translanguaging, this research seeks to contribute to the creation of multilingual-friendly learning environments. Furthermore, it examines how both students and educators can be encouraged to adopt and actively engage with translanguaging as a sustainable, innovative pedagogical approach
Keywords: classroom; čezjezičnost; Hungarian language; madžarski jezik; multilingualism; pedagogika; pedagogy; razred; translanguaging; večjezičnost